Aeroelastic Testing of Span-Wire Traffic Signal Systems - Azzi, Ziad; Matus, Manuel; Elawady, Amal; Zisis, Ioannis; Irwin, Peter; Gan Chowdhury, Arindam (Frontiers in Built Environment, 2020)
Span-wire traffic signals are vulnerable to extreme wind events such as hurricanes and thunder-storms. In past events in the Southeastern Coast of the United States, many failures of span-wire traffic signals were reported. In order to identify their dynamic behavior during extreme wind events and investigate their buffeting response, a large-scale aeroelastic testing was conducted at the NHERI Wall of Wind (WOW) Experimental Facility (EF) at Florida International University (FIU). The WOW is a large-scale open jet wind testing facility, comprised of 12 fans, and capa-ble of simulating winds at speeds up to 70 m/s, corresponding to a Category 5 hurricane. Follow-ing the Froude number criterion, a 1:10 aeroelastic model of a span-wire traffic signal system consisting of two 3-section and one 5-section signals was designed and constructed, based on the properties of its full-scale counterpart. In the testing protocol, various wind directions ranging between 0 and 180 degrees were considered at full-scale wind speeds ranging between 21 m/s and 42.5 m/s. The results of the aeroelastic tests show a similar behavior compared with previous full-scale tests conducted at the WOW. However, an increase in the RMS of accelerations was observed in comparison with those from the full-scale tests. This is attributed to the fact that the aeroelastic model enabled better simulation of low-frequency eddies in the turbulence spectrum compared to the full-scale testing turbulence spectrum.